Diethylenetriamine (DETA)-assisted anchoring of Co3O4 nanorods on carbon nanotubes as efficient electrocatalysts for the oxygen evolution reaction. Issue 4 (8th December 2014) - Zhang, Yu-Xia; Guo, Xin; Zhai, Xue; Yan, Yi-Ming; Sun, Ke-Ning
Abstract : We report the preparation of Co3 O4 @MWCNT with the assistance of DETA and use it as a high performance OER catalyst. Abstract : A Co3 O4 nanorod–multiwalled carbon nanotube hybrid (Co3 O4 @MWCNT) has been fabricated as a highly efficient electrocatalyst for water oxidation in alkaline electrolytes. The well-defined Co3 O4 nanorods were successfully anchored onto mildly oxidized MWCNTs with the assistance of diethylenetriamine (DETA) following a simple route. The as-prepared hybrid possesses a promising BET specific surface area of about 252 m 2 g −1 and shows excellent electrocatalytic activity towards oxygen evolution reactions (OERs) with an onset potential of about 0.47 V vs. Ag/AgCl and an overpotential of 309 mV to achieve a current density of 10 mA cm −2 in 1.0 mol L −1 KOH. In addition, the Co3 O4 @MWCNT catalyst exhibits prominent stability during long-term electrolysis of water. We attribute the enhanced performance to a synergic effect between MWCNTs and Co3 O4 nanorods by gaining insight into the electrochemical properties of the Co3 O4 @MWCNT hybrid. This work offers a useful way to synthesize one-dimensional (1D) metal oxides combined with 1D carbon materials for wide applications in energy storage and conversion.